1996
DOI: 10.1101/gr.6.9.862
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the autosomal dominant juvenile open angle glaucoma (GLC1A) region and evaluation of candidate genes.

Abstract: Juvenile Open Angle Glaucoma {GLCIA) is an autosomal optic neuropathy that has been localized previously to chromosome lq. Here we report the fine mapping of the disease region using YACs and a high density of polymorphic microsatellite markers. This study utilized two large JOAG pedigrees genotyped at 36 loci from chromosome Iq21-q31 to refine the GLC1A locus to a -3-cM region flanked by YAC-derived microsatellite markers DIS3665 and DIS3664. The candidate genes LAMCI, NPRI, and CNR2 were excluded from the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…30,31 From these we selected three single-nucleotide polymorphisms (SNPs) in FAS and two in FASL, and genotyped the 681 family members of 126 American multiplex SLE pedigrees for these as well as a FASL microsatellite in the 3 0 UTR. 32 Of the FAS polymorphisms evaluated, two were located to the promoter: À690C4T (dbSNP rs 2234758) in a possible mutational hotspot and À670G4A (dbSNP rs 1800682) in a GAS (gamma activation site) binding site. 21 The third is a silent mutation in codon214 (ACC to ACT) (dbSNP rs 2234978) in exon 7, which does not lead to an aminoacid change.…”
Section: Association Studiesmentioning
confidence: 99%
“…30,31 From these we selected three single-nucleotide polymorphisms (SNPs) in FAS and two in FASL, and genotyped the 681 family members of 126 American multiplex SLE pedigrees for these as well as a FASL microsatellite in the 3 0 UTR. 32 Of the FAS polymorphisms evaluated, two were located to the promoter: À690C4T (dbSNP rs 2234758) in a possible mutational hotspot and À670G4A (dbSNP rs 1800682) in a GAS (gamma activation site) binding site. 21 The third is a silent mutation in codon214 (ACC to ACT) (dbSNP rs 2234978) in exon 7, which does not lead to an aminoacid change.…”
Section: Association Studiesmentioning
confidence: 99%
“…The markers were ordered based on previously published physical maps of the region. [10][11][12]24,25 The lod scores for the markers are indicated in Table 3. The highest lod score, a ϭ 0, was obtained using an expressed polymorphism identified in the FV gene (see below), which gave a lod score of 7.22.…”
Section: Multipoint Linkage and Haplotype Analysismentioning
confidence: 99%
“…[10][11][12][24][25][26] Polymorphic markers were used to narrow the critical region. The PACs and BACs for contig 195, which completely covers the critical interval, were sequenced by the Sanger Centre.…”
Section: Construction Of the Bac Map For The Critical Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheffield et al (1993) used genetic linkage analysis to map JOAG to chromosome 1. This GLC1A locus was subsequently refined (Sunden et al 1996) and the disease-causing gene was identified using a combination of positional cloning and candidate gene studies (Stone et al 1997). The gene codes for a protein that was initially named trabecular meshwork glucocorticoid response protein (TIGR) .…”
mentioning
confidence: 99%